Catalytic degradation of CWAs with MOF-808 and PCN-222: Toward practical application. Issue 6 (November 2022) - Wu, Shaoxiong; Wang, Lianyuan; Zhu, Haiyan; Liang, Jing; Ge, Liang; Li, Cong; Miao, Ting; Li, Jian; Cheng, Zhenxing
Chemical warfare agents, such as nerve agents (GD and VX) and blister agents (HD), have strong toxicities to mankind. In recent years, zirconium-based metal-organic frameworks have been found to be attractive materials for chemical warfare agent degradation. Among them, metal-organic framework-808 (MOF-808) and porous coordination network-222 (PCN-222) were the best. However, few papers pay attention to their practical application. In this work, we prepared MOF-808 and PCN-222 using water phase and organic solvothermal methods, respectively. Their performance for the catalytic degradation of chemical warfare agents under practical decontamination conditions was studied. The results showed that MOF-808 displayed a high potency for catalytic hydrolysis of VX (10, 000 mg L −1 ) in unbuffered solution. PCN-222 exhibited weaker reactivity with a half-life ( t 1/2 ) of 28.8 min. Their different performances might stem from the different connectivity of the Zr6 nodes and framework structures. The results illustrated that the hydrolysis of high-concentration GD required a strong alkaline buffer to neutralize the hydrolysis product of hydrofluoric acid (HF) to avoid catalyst poisoning. When H2 O2 was used as the oxidant instead of O2, both zirconium-based metal-organic frameworks performed with effective catalytic potency for HD degradation without any special lighting and so was suitable for practical application, whereas the products obtained from HD, such as HDO2 and V-HDO2, still possessed vesicant toxicity. Overall, MOF-808 prepared via a water-phase synthesis performed with effective catalysis for the degradation of high-concentration VX, GD, and HD with t 1/2 of < 0.5, 3.1 and 2.2 min, respectively, exhibiting its potential for practical applications.